Impact of repeat testing of living kidney donors within 14 days of the transplant procedure: a multicenter retrospective survey. Issue 3 (2nd May 2014) - Echenique, I.A.; Cohen, D.; Rudow, D.L.; Ison, M.G.
Abstract Background A transmission of human immunodeficiency virus (HIV) from a live kidney donor prompted recommendations by the New York State Department of Health and the US Centers for Disease Control and Prevention that all live donors undergo additional screening for HIV, hepatitis B virus (HBV), and hepatitis C virus (HCV) within 7–14 days of the donation procedure. There are concerns that re‐screening will result in delays and cancelled transplants. Methods We surveyed live‐donor transplant centers in New York State to assess their screening protocols and outcomes. Nine live‐donor programs (kidney and liver centers) responded. Results All but 1 program has a formal repeat screening policy. Overall, no cancellations occurred, but 2 centers experienced transplantation delays, generally as the result of technician and laboratory procedural mistakes necessitating repeat phlebotomy. Testing is typically coordinated with pre‐surgical visits, additional laboratory tests, and physical examinations. In the initial evaluation, serology was most frequently used (all 9 centers), with few centers utilizing nucleic acid testing (NAT) (HIV NAT, 1; HBV NAT, 2; HCV NAT, 2). Repeat testing modalities varied: HIV antibody (5, 55%), HIV NAT (8, 88%), hepatitis B surface antigen (5, 55%), hepatitis B surface antibody (2, 22%), hepatitis B core antibody (3, 33%), HBV NAT (3, 33%), HCV antibody (3, 33%), and HCV NAT (5, 55%). Conclusion Most respondents have policies to re‐test living donors within 14 days of the transplant procedures. Rarely, centers encountered repeat testing‐associated delays, but no cancellations occurred.